PENDIDIKAN MULTIKULTURAL DI INDONESIA: TANTANGAN DAN STRATEGI PENGEMBANGAN - Arsad Dahri; Julhadi; Sri Wahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The phenomena of discrimination, intercultural stereotypes, the dominance of majority culture in the curriculum, and teachers' lack of understanding of diversity are critical issues in the education system. This study aims to identify multicultural issues in education in Indonesia, analyze their impact on the teaching and learning process, and formulate strategic solutions for the development of effective multicultural education. The methodology used is a literature review with descriptive-qualitative analysis of various literature sources, scientific journals, and policy documents related to multicultural education. The results of the study indicate that multicultural education has not been optimally implemented due to an exclusive curriculum, insufficient teacher training, and weak educational policies that are unresponsive to diversity. As a result, students from minority groups experience marginalization, decreased motivation to learn, and feelings of alienation.